From Quantity To Quality: Massive Molecular Dynamics Simulation of Nanostructures under Plastic Deformation in Desktop and Service Grid Distributed Computing Infrastructure - Gatsenko, Olexander; Bekenev, Lev; Pavlov, Evgen; Gordienko, Yuri G. (Computer Science, 2013)
The distributed computing infrastructure (DCI) on the basis of BOINC andEDGeS-bridge technologies for high-performance distributed computing is usedfor porting the sequential molecular dynamics (MD) application to its paral-lel version for DCI with Desktop Grids (DGs) and Service Grids (SGs). Theactual metrics of the working DG-SG DCI were measured, and the normal dis-tribution of host performances, and signs of log-normal distributions of othercharacteristics (CPUs, RAM, and HDD per host) were found. The practicalfeasibility and high eﬃciency of the MD simulations on the basis of DG-SG DCIwere demonstrated during the experiment with the massive MD simulations forthe large quantity of aluminum nanocrystals ( ∼ 102–103). Statistical analysis(Kolmogorov-Smirnov test, moment analysis, and bootstrapping analysis) ofthe defect density distribution over the ensemble of nanocrystals had shownthat change of plastic deformation mode is followed by the qualitative changeof defect density distribution type over ensemble of nanocrystals. Some limita-tions (ﬂuctuating performance, unpredictable availability of resources, etc.) ofthe typical DG-SG DCI were outlined, and some advantages (high eﬃciency,high speedup, and low cost) were demonstrated. Deploying on DG DCI al-lows to get new scientiﬁc quality from the simulated quantity of numerousconﬁgurations by harnessing suﬃcient computational power to undertake MDsimulations in a wider range of physical parameters (conﬁgurations) in a muchshorter timeframe.